Teoria Hegeliana da pena e administração da justiça - Arsego, Djonatan (My University, 2017)
The study developed in this dissertation deals with the Hegelian concept of the administration of justice from the work entitled “Filosofia do Direito” (legal philosophy). (FD, 2003). This Hegelian conception of the administration of the law is part of the concept of the civil society encompassed in ethics, the third part of the philosophy of law. This subsection is composed of paragraphs 209-229, and deals with the application of the law. This paper examines if the institution of the law is real and effective for the society and for its citizens; how the laws are formed and applied in social groups, and why they are so important to the stability and coexistence of people in a state according to the Hegelian theory of law. But how can it be said that the Hegelian right, in its theory of punishment, is stable, in view of the variations in the application of laws? Also, in view of the different ways offenders are judged? These answers will be given in court by the penalty chosen, which is given to each particular case, analyzing the intention for which the citizen has deviated from interacting with other members of society and seeing the damage caused by the offenders. This work also deals with the problems of the "right to say no" and the "right of necessity or emergency". It also incorporates the concepts of intent and unintentional guilt present in Hegelian morality. For the penalty to be effective, it is required that society sees it in the form of codes, which will allow all citizens to recognize them as models, and at the same time as costumes needed for a good living. Therefore, it is important to understand how the laws are formed and actualized in society, as this is the reason for their existence.
O estudo desenvolvido nesta dissertação trata do conceito hegeliano da administração da justiça a partir da obra Filosofia do Direito. (FD, 2003). Essa concepção hegeliana da administração do direito faz parte do conceito de sociedade civil englobada na Eticidade, a terceira parte da Filosofia do Direito. Essa subseção é composta pelos parágrafos 209 a 229, e trata da aplicação do direito. Esta dissertação examina se a instituição do Direito é real e efetiva para a sociedade e para os seus cidadãos; como se formam e se aplicam as leis na sociedade e para seus cidadãos, e por que as mesmas são tão importantes para a estabilidade e para o convívio das pessoas em um Estado segundo a teoria do direito hegeliano. Mas, como se pode dizer que o direito hegeliano, em sua teoria da pena, é estável, tendo em vista as variações na aplicação das leis? E, também em vista do diferente modo como os delinquentes são julgados? Estas respostas serão dadas no tribunal pela pena, que é sancionada a cada caso particular, analisando a intenção pela qual o cidadão se desviou do convívio com os demais membros da sociedade e vendo os danos causados por um infrator. O trabalho também trata dos problemas do “direito de dizer não” e do “direito de necessidade ou emergência”. Também retoma os conceitos de dolo e culpa presentes na moralidade hegeliana. Mas, para que a pena seja efetiva, requer-se que a sociedade possua códigos que permitam que todos os cidadãos reconheçam as leis como guias, assim como os costumes para o bom convívio. Portanto, é importante compreender como as leis se formam e se efetivam na sociedade, o que são e o porquê de sua existência.
Keywords: Filosofia; Ética; Direito - Filosofia; Justiça (Filosofia); Crime; Philosophy; Ethics; Philosophy of law; Justice (Philosophy)